Gastroprotector effect from Clinopodium bolivianum (Benth.) Kuntze “inca muña” on induced gastric injury in mice - Herrera, Oscar (2015)
The objective of the study was to determine the effect gastroprotector of ethanolic extract of Clinopodium bolivianum on gastric injuries induced in mice, were used 36 albino male mice Balb/C, between 30-35 g, previously fasted for 24 h, only with water ad libitum. The gastric were injuries induced with indomethacin 2,5 mg/Kg (s.c.) one hour before administering the extract, complementing 20 minutes after with ethanol 96%, 0,1 mL orally. The experimental design was composed by: G1 negative control; G2 positive control; G3 ranitidine 50 mg Kg; G4, G5 y G6 extract 50, 150 y 300 mg/kg, respectively. An hour later, the stomachs were extracted and evaluated as harmful signs: inflammation, hemorrhagic bands and gastric ulcer; and then histological studies were performed. In the results Inca muña ethanolic extract showed secondary metabolites as phenolic compounds, flavonoids, triterpenos and alkaloids. It was got gastroprotector effect to the 300 mg/Kg dose comparable to positive control group (U Mann Whitney; p<0,001). The stomach histology evidenced by pasting in apexes and mononuclear infiltration. Was concluded that ethanolic extract of Clinopodium bolivianum presents gastroprotector activity at 300 mg/Kg on gastric injuries induced in mice.